Weighted symbol-flipping decoding for non-binary LDPC codes based on average probability and stopping criterion - Rui GUO; Chun-yu LIU; Mei-jie WANG; Peng PAN; Jian-rong BAO; Chun-sheng GUO (Tongxin xuebao)
In order to improve the decoding performance and reduce the decoding complexity of weighted symbols flipping decoding algorithm for nonbinary low density parity-check(LDPC)code, a weighted symbols flipping decoding for nonbinary LDPC codes based on average probability and stopping criterion was proposed. The algorithm puts the average probability of all the information nodes adjacent to the check node as weights to make the flipping-function more effectively and improve the efficiency of the flipping-symbols, and then improves the decoding performance. At the same time, the algorithm adds a stopping criterion controlling decoding iterations to further improve the decoding speed. Simulation results show that compared to WSF algorithm, NSCWSF algorithm(Osc=10)and NSCWSF algorithm(Osc=6), the new algorithm proposed(O =10)is gotten about 0.68dB, 0.83dBand 0.96dBgain at the symbol error rate of 10-5in thesc presence of additive white Gaussian noise(AWGN), meanwhile, the average number of decoding iterations is also reduced by 78.60%～79.32%, 74.89%～75.95% and 67.2%～70.8%, respectively.